Monitoring honey adulteration with sugar syrups using an automatic pulse voltammetric electronic tongue. (September 2018) - Sobrino-Gregorio, Lara; Bataller, Román; Soto, Juan; Escriche, Isabel
Abstract: The new tendency to detect adulterated honey is the development of affordable analytical equipment that is in-line and manageable, enabling rapid on site screening. Therefore, the aim of this work was to apply an electronic tongue based on potential multistep pulse voltammetry, in combination with multivariate statistical techniques to detect and quantify syrup in honey. Pure monofloral honey (heather, orange blossom and sunflower), syrup (rice, barley and corn), and samples simulating adulterated honey with different percentages of syrup (2.5, 5, 10, 20 and 40) were evaluated. An automatic, electrochemical system for cleaning and polishing the electronic tongue sensors (Ir, Rh, Pt, Au) significantly improved the repeatability and accuracy of the measurements. PCA analysis showed that the proposed methodology is able to distinguish between types of pure honey and syrup, and their different levels of adulterants. A subsequent PLS analysis successfully predicted the level of the adulterants in each honey, achieving good correlations considering the adjusting parameters. The best results being for sunflower honey adulterated with corn syrup and heather honey with barley syrup (r 2  = 0.997), and heather with corn (r 2  = 0.994) whereas the weakest was found for heather honey adulterated with brown rice syrup (r 2  = 0.763) and orange blossom honey with corn syrup (r 2  = 0.879). The measurement system here proposed could be a very quick and effective option for the honey packaging sector with the finality of providing information about a characteristic as important as the adulteration of honey. Highlights: Pulse voltammetry can be useful in detecting and quantifying syrups in honey. This methodology can distinguish between pure honeys and syrups. This methodology can distinguish among different levels of adulterants. PLS analysis can predict the level of adulteration with syrups in honeys.